Lipase-Catalyzed Synthesis of Sugar Esters in Honey and Agave Syrup - Siebenhaller, Sascha; Gentes, Julian; Infantes, Alba; Muhle-Goll, Claudia; Kirschhöfer, Frank; Brenner-Weiß, Gerald; Ochsenreither, Katrin; Syldatk, Christoph (Frontiers in Chemistry, 2018)
Honey and agave syrup are high quality natural products and consist of more than 80% sugars. They are used as sweeteners, and are ingredients of cosmetics or medical ointments. Furthermore, both have low water content, are often liquid at room temperature and resemble some known sugar-based deep eutectic solvents. Since it has been shown that it is possible to synthesize sugar esters in these deep eutectic solvents, in the current work honey or, as vegan alternative, agave syrup are used simultaneously as solvent and substrate for the enzymatic sugar ester production. For this purpose, important characteristics of the herein used honey and agave syrup were determined and compared with other available types. Subsequently, an enzymatic transesterification of four fatty acid vinyl esters was accomplished in ordinary honey and agave syrup. Notwithstanding of the high water content for transesterification reactions of the solvent, the successful sugar ester formation was proved by thin-layer chromatography and compared to a sugar ester which was synthesized in a conventional deep eutectic solvent. For a clear verification of the sugar esters, mass determinations by ESI-Q-ToF experiments and a NMR analysis were done. These environmentally friendly produced sugar esters have the potential to be used in cosmetics or pharmaceuticals, or to enhance their effectiveness.